Comparison of Concept Understanding Using the Scramble Learning Method Between Courselab Interactive Media and Microsoft Powerpoint Media - Qodri, Nurul; Hassan, Qusay Mohammed Ali (Tekno - Pedagogi : Jurnal Teknologi Pendidikan, 2023)
This study aims to analyze the difference in concept understanding between students who use CourseLab and Microsoft PowerPoint interactive learning media in the Scramble learning method in class XI Mathematics Natural Sciences State Islamic Senior High School Wajo. The study used a quasi-experimental design with a Non Equivalent Control Group Design, involving two classes as samples taken by convenience sampling technique. The experimental class learns using CourseLab, while the control class uses PowerPoint. The results showed that the experimental class obtained a more significant increase in concept understanding compared to the control class, which was shown through higher posttest and N-gain scores. The results of the t-test analysis in the posttest showed a significant difference between the two groups (p < 0.05), supporting the effectiveness of CourseLab in improving concept understanding. The novelty of this research lies in the use of CourseLab media in the Scramble learning method, contributing to the development of technology-based interactive learning media for active learning in high schools.